Predictive Value of Second-Trimester Maternal Lipid Profiling in Early-Onset Pre-eclampsia: A Prospective Cohort Study and Nomogram - Li, Juan; Lu, Juefei; Wang, Mengni; Hu, Wen; Jin, Neng; Li, Xingmiao; Zhao, Baihui; Luo, Qiong (Frontiers in Medicine, 2021)
Purpose: Maternal lipid profile in second trimester has rarely been investigated in the risk assessment for preeclampsia (PE). Since early-onset PE often companied by much worse clinical outcomes, thus, we aimed to evaluate the predictive value of second-trimester maternal lipid profiling for early-onset PE. Methods: A prospective cohort study was conducted to measure the second-trimester maternal lipid profile of pregnant women from January to December 2019. The pairwise association between maternal lipid profile and PE onset or pregnancy termination time was quantified. Multiple logistic regression was preformed to define risk factors for early-onset PE, and a nomogram for early-onset PE was developed. The net benefit of our model was evaluated by calibration curve and decision curve analyses. Results: We enrolled 5908 pregnant women and they were divided into healthy (n = 5789), late-onset PE (n = 64), and early-onset PE (n = 55) groups. Total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-c) were elevated in patients with PE, while high-density lipoprotein cholesterol (HDL-c) was decreased in patients with PE. TC, TG, and LDL-c were negatively correlated with PE onset time or gestational week at delivery. Receiver operating characteristic curves (ROC) defined the cutoff values of TG and HDL-c, and the final regression model included five statistically significant risk predictors for early-onset PE( maternal age of ≥35 years, multipara, pre-pregnancy body mass index(BMI) ≥25 kg/m2, second trimester TG≥2.59mmol/L and second trimester HDL-c≤ 2.03mmol/L. The nomogram had an excellent diagnostic performance (area under the curve = 0.912, sensitivity = 92.7%, and specificity = 76%) and was further validated with good calibration and positive net benefits in a decision curve analysis. Conclusions: An abnormally increased TG concentration and a decreased HDL-c concentration might serve as predictors of early-onset PE. Whether blood lipid-lowering measures can improve severe PE prognosis require further clarification.